The analysis of relationship between experiential marketing, service quality, visitors’ satisfaction, and revisit intention: study on tourism industry - Adinda Sekar Ramdhani; Sri Rahayu Tri Astuti (Diponegoro International Journal of Business, 2019)
This study aims to analyze the impact of experiential marketing and service quality on revisit intention which visitors’ satisfaction as mediating variable.  The sample of our study was the 135 visitors’ of Grand Puri Maerokoco, one of the tourism sites in Semarang, Central Java, Indonesia. The result of SEM analysis on those data shows that experiential marketing and service quality have indirect, positive, and significant effect on revisit intention, using visitors’ satisfaction as intervening variable. However, experiential marketing and service quality are not significantly affected revisit intention. Discussions and implications of this study are presented.